Anti-nociceptive Activity of Ethnomedicinally Important Analgesic Plant Isodon rugosus Wall. ex Benth: Mechanistic Study and Identifications of Bioactive Compounds - Zeb, Anwar; Ahmad, Sajjad; Ullah, Farhat; Ayaz, Muhammad; Sadiq, Abdul (Frontiers in Pharmacology, 2016)
Isodon rugosus Wall. ex Benth. is extensively used as traditional medicine for the management of various types of pain including tooth ache, gastric pain, abdominal pain, ear ache and generalized body pain. The current study is designed to scientifically verify the purported uses of I. rugosus as analgesic agent and to figure out its possible mechanism of action. Bioactive compounds responsible for analgesic activity were identified using GC and GC-MS analysis. Analgesic potentials were evaluated using acetic acid induced writhing, hot plate test and formalin induced paw licking test. In acetic acid induced writhing chloroform fraction (Ir.Chf) exhibited 53% analgesia while formalin test displayed 61% inhibition at phase-I and 45% at phase-II respectively at a dose of 100 mg/kg. Similarly, in hot plate test Ir.Chf displayed average reaction time of 7 minute at 15, 30, 45 and 60 min intervals. The possible mechanism of action was found to be the central pathway via opioidergic receptors as the mice showed morphine like analgesic activity at pre-administration of naloxone (opioid antagonist) in hot plate and formalin tests. In GC-MS analysis, 83 compounds were identified among which 8 compounds including benzyl alcohol, sebacic acid, myristic acid, phytol, sugiol, Tocopherol, α-Amyrin and stigmasterol were sorted out as previously reported analgesic compounds. Current study revealed that analgesic potential of I. rugosus can attributed to the presence of analgesic compounds. It may also be concluded that opioids receptors are involved in the analgesic mechanism of I. rugosus due to effective antagonism of nalaxone.